Search for resonances decaying into photon pairs in 139 fb−1 of pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Andrei, George Victor; Bartels, Falk; Bolz, Arthur; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Klassen, Martin; Krishnan, Anjali; Mkrtchyan, Tigran; et al. (Physics letters, 2021)
Searches for new resonances in the diphoton final state, with spin 0 as predicted by theories with an extended Higgs sector and with spin 2 using a warped extra-dimension benchmark model, are presented using 139 fb−1 of √s=13 TeV pp collision data collected by the ATLAS experiment at the LHC. No significant deviation from the Standard Model is observed and upper limits are placed on the production cross-section times branching ratio to two photons as a function of the resonance mass.
*The ATLAS Collaboration: G. Aad, V. Andrei, F. Bartels, A.E. Bolz, M.M. Crzurylo, S.J. Dittmeier, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M. Klassen, A. Krishnan, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, A. Schoening, H.-C. Schultz-Coulon, T. Spieker, R. Stamen, P. Starovoitov, S.M. Weber, M. Wessels, L. Vigani, X. Yue [und 2912 weitere Personen]
Im Titel ist die Zahl -1 hochgestellt
Im Titel steht der Buchstabe s unter dem Wurzelzeichen
Gesehen am 30.11.2021